Design of Imide Oligomer‐Mediated MOF Clusters for Solar Cell Encapsulation Systems by Interface Fusion Strategy. Issue 9 (29th January 2023) - Wu, Minghong; Li, Jiaxin; Zhang, Xi; Liu, Shumei; Zhao, Jianqing; Xie, Weiqi
Abstract: Dielectric encapsulation materials are promising for solar cell areas, but the unsatisfactory light‐management capability and relatively poor dielectric properties restrict their further applications in photovoltaic and microelectronic devices. Herein, an interface fusion strategy to engineer the interface of MOF (UiO‐66‐NH2 ) with anhydride terminated imide oligomer (6FDA‐TFMB) is designed and a novel MOF cluster (UFT) with enhanced forward scattering and robust porosity is prepared. UFT is applied as an optical and dielectric modifier for bisphenol A epoxy resin (DGEBA), and UFT epoxy composites with high transmittance (>80%), tunable haze (45–58%) and excellent dielectric properties can be prepared at low UFT contents (0.5–1 wt%), which delivers an optimal design for dielectric encapsulation systems with efficient light management in solar cells. Additionally, UFT epoxy composites also show excellent UV blocking, and hydrophobic, thermal and mechanical properties. This work provides a template for the synthesis of covalent bond‐mediated nanofillers and for the modulation of haze and dielectric properties of dielectric encapsulation materials for energy systems, semiconductors, microelectronics, and more. Abstract : A novel core–shell nanofiller UFT with enhanced forward scattering and robust porosity is achieved by using an interfacial fusion strategy to engineer the interface of MOFs with imide oligomers, thus creatively endowing the UFT encapsulation materials with outstanding light‐management function (tunable haze and forward scattering) and simultaneously enhanced dielectric properties, which show promising applications in solar cells.